Ответ:3)
1
2
3
4)
Пошаговое объяснение:
Всё, надеюсь помог, не обманывай с баллами, далось всего 6
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:3)
1
2
3
4)
1![(1 - \frac{3}{5} ) + 2 \frac{1}{5} = \frac{2}{5} + 2 \frac{1}{5} = 2 \frac{3}{5} (1 - \frac{3}{5} ) + 2 \frac{1}{5} = \frac{2}{5} + 2 \frac{1}{5} = 2 \frac{3}{5}](https://tex.z-dn.net/?f=%281%20-%20%20%5Cfrac%7B3%7D%7B5%7D%20%29%20%2B%202%20%5Cfrac%7B1%7D%7B5%7D%20%20%3D%20%20%5Cfrac%7B2%7D%7B5%7D%20%20%2B%202%20%5Cfrac%7B1%7D%7B5%7D%20%20%3D%202%20%5Cfrac%7B3%7D%7B5%7D%20)
2
3
Пошаговое объяснение:
Всё, надеюсь помог, не обманывай с баллами, далось всего 6